Precursory velocity changes prior to the 2019 paroxysms at Stromboli volcano, Italy, from coda wave interferometry - Alexander Yates; Corentin Caudron; Aurélien Mordret; Philippe Lesage; Andrea Cannata; Flavio Cannavo; Thomas Lecocq; Virginie Pinel; Lucia Zaccarelli (Volcanica)
Open-conduit basaltic volcanoes are susceptible to sudden transitions from mild activity to violent explosive eruptions with little to no warning. Such was the case at Stromboli in the summer of 2019, when two paroxysmal explosions occurred within approximately two months (July 3 and August 28). We apply coda wave interferometry to identify possible transitions in behavior in the build-up to these events, computing seismic velocity changes using five broadband seismic stations on the volcano between 2013–2022. This timeframe encompasses a range of volcanic activity including effusive activity, major explosions and paroxysms. Cross-correlation functions are computed both between pairs of stations and single-station cross-components in multiple frequency bands that allow the sampling of different depths (between approximately 100–1000 m) within the plumbing system. Shallow velocity changes (1–2 Hz and 2–4 Hz) reveal mid-to-long term precursors prior to the paroxysms in 2019. For example, we observe that 2–4 Hz velocities recorded at the station closest to the active crater show an increase of 0.2–0.3 % relative to velocities recorded at other stations. This increase is largely accumulated from mid-2017, coinciding with previously observed heightened activity at the volcano, peaking approximately one month prior to the first paroxysm. A long-term decrease is also observed in deeper velocity changes (0.5–1.0 Hz) during the same time interval. It is hypothesized that these changes represent greater magma overpressure from increased volatile input from depth. The different response in the shallow subsurface may reflect a local response due to the same source within the vicinity close of the crater terrace. These findings illustrate how coda wave interferometry can provide meaningful insights into the evolving dynamics of open-conduit basaltic volcanoes.